IMPLEMENTATION OF E-CARDS FOR BUDDHIST CLERKS IN IMPROVING SERVICE EFFECTIVENESS AND BUDGET EFFICIENCY AT THE DIRECTORATE GENERAL (DITJEN) OF BUDDHIST COMMUNITY GUIDANCE (BIMAS) - Sobiyanto,; Jansen Wiratama,; Heru Soetanto Putra,; Daril Willianson Hakim,; Herman,; Sobita, (Jurnal Bakti Masyarakat Indonesia, 2025)
The rapid development of technology today has had a major impact on various aspects of human life. One sector that has greatly benefited from this progress is the business world and companies. Technology not only facilitates access to information and communication, but also significantly increases efficiency and effectiveness in various company operational processes. The institutional section of the DITJEN BIMAS Buddha prints Buddhist clergy cards using a desktop information system so that card applications take time and card printing requires a budget for PVC cards and ink every year. The Director General as the highest leader in the DITJEN BIMAS Buddha instructed to carry out effectiveness and efficiency in printing the Buddhist clergy cards. To overcome this problem, a web-based clergy e-card information system is proposed that can upload documents online and produce clergy cards in the form of files with the extension .pdf. With this card, applicants can upload files online and print cards independently so that the institutional section of the DITJEN BIMAS Buddha does not need to budget for printing the clergy cards. The implementation results show that the Buddhist clergy e-card information system is able to provide solutions in carrying out budget effectiveness and efficiency in the institutional section. From the survey results, it can be seen that 100% of respondents strongly agree that this system can increase effectiveness and make budget costs more efficient. The final part of the survey, 100% of the institutional section strongly agrees with the implementation of the clergy e-card information system.